PERILAKU GAYA HIDUP REMAJA BERISIKO TERKAIT PENYAKIT TIDAK MENULAR DI INDONESIA - Salimar Yunas; Budi Setyawati; Rika Rachmawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2021)
ABSTRACT Adolescents in Indonesia as much as 24,01 percent can be used as agents of change for the lowering in non-communicable diseases (NCD) in the future. In addition risk of NCD having an impact on increasing morbidity, mortality, and disability among the community, also have an impact on increasing economic burdens both at the individual and national level. The purpose of this study is to find out the proportion of adolescent health-nutrition behavior at risk of NCD, so it can be used as a basis in providing nutrition-health education to prevent non-communicable diseases in adulthood. The study was analyzed based on Riskesdas 2013 and SKMI 2014 data. The samples were all teenagers aged 13-18 years sampled in Riskesdas 2013 and SKMI 2014. The variables analyzed were national and health behavior at risk of NCD including smoking behavior, physical activity, GGL intake (sugar, salt, fat), blood pressure, and central obesity. The riskiest nutritional behavior was excessive sodium intake (52.1%), excessive fat intake (26.1%), consumption of fruits and vegetables as much as 5 servings a day was only 1.5 percent. Health behaviors risk physical activity less than 30 minutes every day (66.0%) and smoking (10.0%). Lifestyle behaviors in the adolescent that are at risk for NCD were high intake of salt, excessive fat, consumption of fruits and vegetables less, smoking behavior, and lack of physical activity. It is necessary to promote healthy living behavior policies starting from home and school to increase knowledge about the risk of NCD and to change health behavior in adolescents. ABSTRAK Remaja di Indonesia sebanyak 24,01 persen dapat dijadikan sebagai agent of change untuk penurunan angka penyakit tidak menular (PTM) di masa datang. Risiko PTM, disamping berdampak pada meningkatnya morbiditas, mortalitas, dan disabilitas di kalangan masyarakat, juga berdampak pada meningkatnya beban ekonomi baik di tingkat individu maupun di tingkat nasional. Tujuan penelitian mengetahui proporsi perilaku gaya hidup remaja yang berisiko terhadap PTM, sehingga dapat digunakan sebagai dasar dalam memberikan edukasi gizi-kesehatan dalam upaya mencegah penyakit tidak menular saat usia dewasa. Analisis lanjut data Riskesdas 2013 dan SKMI 2014. Sampel adalah semua remaja berusia 13-18 tahun yang menjadi sampel di Riskesdas 2013 dan SKMI 2014. Variabel yang dianalisis adalah perilaku gizi dan kesehatan berisiko terhadap PTM meliputi: konsumsi buah dan sayur, kebiasaan merokok, aktivitas fisik, asupan GGL (gula, garam, lemak), tekanan darah, dan obesitas sentral. Perilaku gaya hidup berisiko PTM yang paling besar proporsinya pada remaja adalah kurang konsumsi buah dan sayur (98,5%), konsumsi natrium yang berlebihan (52,1%), konsumsi lemak berlebihan (26,1%),kurang aktivitas fisik (66,0%) dan merokok (10,0%). Perilaku gaya hidup berisiko pada remaja yaitu konsumsi buah dan sayur kurang, asupan garam berlebihan, konsumsi lemak berlebihan, perilaku merokok dan kurangnya aktivitas fisik. Perlu kebijakan promosi perilaku hidup sehat yang di mulai dari rumah dan sekolah untuk meningkatkan pengetahuan tentang risiko PTM. [Penel Gizi Makan 2021, 44(1):11-20]